Porous textured ceramics with controlled grain size and orientation - Behera, Rohit Pratyush (2021)
Texture in dense or porous ceramics can enhance their functional and structural properties. Current methods for texturation employ anisotropic particles as starting powders and processes that drive their orientation into specific directions. Using ultra-low magnetic fields combined with slip casting, it is possible to purposely orient magnetically responsive particles in any direction. When those particles are suspended with nanoparticles, templated grain growth occurs during sintering to yield a textured ceramic. Yet, the final grains are usually micrometric, leading weak mechanical properties. Here, we explore how to tune the grain orientation size using magnetic slip casting and templated grain growth. Our strategy consists in changing the size of the anisotropic powders and ensuring that magnetic alignment and densification occurs. The obtained ceramics featured a large range of grain anisotropy, with submicrometric thickness and anisotropic properties. Textured ceramics with tunable grains dimensions and porosity are promising for filtering, biomedical or composite applications.